2009
DOI: 10.1136/pgmj.2008.074666
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured abdominal aortic aneurysm: a surgical emergency with many clinical presentations

Abstract: Ruptured abdominal aortic aneurysm (AAA) is one of the most fatal surgical emergencies, with an overall mortality rate of 90%. Most AAAs rupture into the retroperitoneal cavity, which results in the classical triad of pain, hypotension, and a pulsatile mass. However, this triad is seen in only 25-50% of patients, and many patients with ruptured AAA are misdiagnosed. It is likely that different sites of rupture of AAA determine a variety of common and uncommon clinical presentations, the recognition of which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 63 publications
3
89
0
14
Order By: Relevance
“…18 Previous work demonstrated that the sites of rupture revealed higher quantities of MMP-8 and MMP-9 and more neovascularization compared with the intact ventral walls of the same patients. 19,20 This indicates that the laterally increased quantity of microvessels and active proteases in intact AAAs described in present study predisposes this region of the AAA as being more vulnerable to rupture.…”
Section: Discussionmentioning
confidence: 97%
“…18 Previous work demonstrated that the sites of rupture revealed higher quantities of MMP-8 and MMP-9 and more neovascularization compared with the intact ventral walls of the same patients. 19,20 This indicates that the laterally increased quantity of microvessels and active proteases in intact AAAs described in present study predisposes this region of the AAA as being more vulnerable to rupture.…”
Section: Discussionmentioning
confidence: 97%
“…Undergoing a vascular surgical procedure was a predictor of mortality for patients receiving surgery within 24 hours of admission. Investigation into these procedures demonstrated that 47% of patients receiving a vascular surgery procedure within 24 hours had a postoperative diagnosis of a ruptured abdominal aortic aneurysm, which has been shown elsewhere to have a 90% mortality rate [19]. Interestingly, the type of procedure performed was not associated with inpatient mortality for patients undergoing surgery at least 24 hours after admission.…”
Section: Discussionmentioning
confidence: 95%
“…10 Considera-se que apresenta critério operatório quando o seu diâmetro transversal é superior a 5,5 cm ou se documenta um crescimento superior a 0,5 cm no período de seis meses, independentemente de qual o seu diâme-tro. 11 A sua identificação precoce e correção atempada constituem assim uma necessidade, numa tentativa de prevenir um desfecho potencialmente trágico.…”
Section: Discussionunclassified